Perception on Prolonged Standing Work in Electronic Manufacturing Company - Mohamad, Norlizaa; Mohd Rohani, Jafri; Abdul Rahman, Ismail; Amira Mat Zuki, Anis (International Journal of Engineering and Technology, 2018)
Prolonged standing is one of the common activities in electronic industry as the task requirement. Prolonged standing can cause discomfort on the body of the workers and can lead to injury and occupational disease. The purpose of this study is to investigate standing workers perception on the fatigue and the discomfort on their respective body region for 12 hours working time. The subjects are the 80 workers with a good health condition and at least 6 months tenure. The subject data are collected via questionnaires and Likert scale to define the discomfort, pain, and fatigue. The workers were interviewed regarding their job and perceived fatigue discomfort. The results show the domination of the lower body region with the higher mean at the lower back, legs, and foot ankle. No statistically significant differences were found between the job tenure and body part discomfort pain and fatigue. There is a significant relation between gender and discomfort pain on legs and foot ankle. The result also shows a strong relation between age and the discomfort body parts of thigh and foot ankle. The perceptions of the workers towards discomfort pain and fatigue cause by prolonged standing during performing the task. The results from this study will provide a view for industrial consultants or ergonomist with evidence to support for ergonomic interventions for prolonged standing activity such as job rotation and work-rest schedule.Â